High Loaded Mounts for Vibration Control Using Magnetorheological Fluids: Review of Design Configuration - Xuan Phu Do; Seung-Bok Choi (Shock and Vibration)
Design configurations of high loaded magnetorheological (MR in short) mounts are reviewed and discussed. The configurations are analyzed on the basis of three operating modes of MR fluid: flow mode, shear mode, and squeeze mode. These modes are significantly important to develop new type of mounts and improve the efficiency of vibration control. In this paper, advantages and disadvantages of each operation mode are analyzed on the basis of ability of designing high loaded mounts. In order for analysis, the field-dependent damping force equations for typical cross sections of mounts are firstly investigated while maintaining original equations of these cross sections. As a subsequent step, simulation tools for the high loaded mounts are investigated and discussed. These tools which are developed from the analyzed method are expressed as functions of various design parameters such as inside pressure, magnetic field, dimension, stiffness, and damping. These tools are essential for accurate design of MR mount and for careful checking of the operation capability before manufacturing the mounts. This paper can provide very useful information and guidelines to determine an appropriate design configuration of high loaded mounts whose vibration control performances depend on the operational mode of MR fluid.